Perioperative Anaesthetic Management and Outcomes in Bariatric Surgery: A Seven-year Retrospective Cohort Study at Hospital Pakar Universiti Sains Malaysia - Kandasamy, Kavitha; Ab Mukmin, Laila; Che Omar, Sanihah; W Hassan, W Mohd Nazaruddin; Esa, Umairah; Mohd Nizam; Zakaria, Zaidi; Wan Muhd Shukeri, Wan Fadzlina (Malaysian Journal of Medical Sciences, 2025)
Background: Perioperative anaesthetic management in bariatric surgery presents unique challenges due to patient comorbidities and elevated perioperative risk. This study aimed to evaluate perioperative anaesthetic practices and determine factors associated with postoperative high-dependency unit (HDU) admissions among bariatric surgery patients at a tertiary centre in Malaysia. Methods: A retrospective cohort study was conducted involving 104 adult patients who underwent elective bariatric surgery between 2016 and 2022 at Hospital Pakar Universiti Sains Malaysia. Demographic, clinical, surgical, and anaesthetic data were collected. Univariate and multivariate logistic regression analyses were performed to identify factors associated with postoperative HDU admission. Results: The mean age of the patients was 42.5 years (standard deviation [SD] = 9.7), with a female predominance (68.3%) and a mean body mass index (BMI) of 49.6 kg/m² (SD = 11.3). Obstructive sleep apnoea (OSA) (56.7%) was the most common comorbidity. Laparoscopic sleeve gastrectomy was the most frequently performed procedure (66.3%). The overall HDU admission rate was 34.6%, with a decreasing trend from 2020 to 2022. Patients admitted to the HDU had a significantly higher BMI, more comorbidities, longer operative times, and a higher prevalence of OSA. Multivariate analysis identified OSA (adjusted odds ratio [OR] = 2.6; 95% confidence interval [CI]: 1.003–6.781; P = 0.049) and longer duration of surgery (adjusted OR = 2.1; 95% CI: 1.018–4.375; P = 0.045) as independent predictors of HDU admission. There were no cases of difficult intubation, postoperative pneumonia, or in-hospital mortality. Conclusion: Obesity-related diseases, particularly OSA, were highly prevalent. The incidence of difficult intubation was negligible with the use of video laryngoscopy in the ramped position. The HDU admission rates were higher than international benchmarks, influenced primarily by BMI, comorbidities, and surgery duration.